KARAKTERISTIK FISIK DAN ORGANOLEPTIK TEPUNG DAGING KERANG BAMBU (Solen sp.) DENGAN BAHAN PERENDAM YANG BERBEDA - Ninis Trisyani; Titiek Indhira Agustin; Rindang Hayati Ningrum (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2021)
ABSTRACTBamboo shells (Solen sp.) is sea shells that have high nutritional content so that they have the potential to be developed as a food source in various product diversifications, such as bamboo clam meat flour. The research aims at determining bamboo clam’s meat flour characteristics physically and organoleptically by using various soaking ingredients. The results show that the different soaking materials have no significant effect on the yield of bamboo clam’s meat meal (Solen sp.) with a significance value (p = 0.054). The highest yield of bamboo clam’s meat flour (Solen sp.) is bamboo clam’s meat flour soaked in lemon lime with a value of 11.5%. The results of testing the characteristics of the color of the bamboo clam’s meat flour physically show that the whiteness of the bamboo clam’s meat flour (Solen sp.) soaked using lime, lemon, lime “limau:, and kaffir lime is 55.73%, 54.19%, 55.09%, 53.72%. The organoleptically testing results (color, texture, aroma) of bamboo clam’s meat flour, and the taste of cheese sticks are that were the most preferred by the panelists were bamboo clam’s meat flour soaked in lemon with an organoleptic average value of 4.1 on an organoleptic scale of 1 - 5.Keywords: Shellfish flour, Shellfish organoleptic, Solen sp., whiteness level of flour.ABSTRAKKerang bambu (Solen sp.) merupakan kerang laut yang mempunyai kandungan gizi tinggi sehingga berpotensi untuk dikembangkan sebagai sumber pangan dalam berbagai diversifikasi produk yaitu tepung daging kerang bambu. Tujuan penelitian ini untuk mengetahui karakteristik fisik dan organoleptik tepung daging kerang bambu dengan menggunakan berbagai bahan perendam. Hasil penelitian menunjukkan bahan perendam yang berbeda memberikan pengaruh yang tidak berbeda nyata terhadap rendemen tepung daging kerang bambu (Solen sp.) dengan nilai signifikansi (p=0.054). Rendemen tepung daging kerang bambu (Solen sp.) yang paling besar adalah tepung daging kerang bambu yang direndam menggunakan jeruk lemon dengan nilai sebesar 11,5%. Hasil uji karakteristik fisik warna tepung daging kerang bambu menunjukkan bahwa derajat putih tepung daging kerang bambu (Solen sp.) yang direndam menggunakan jeruk nipis, jeruk lemon, jeruk limau, jeruk purut berturut-turut sebesar 55,73%, 54,19%, 55,09%, 53,72%. Hasil uji organoleptik (warna, tekstur, aroma) tepung daging kerang bambu, dan rasa stick keju yang paling disukai panelis yaitu tepung daging kerang bambu yang direndam menggunakan jeruk lemon dengan nilai rata-rata organoleptik 4.1 pada skala organoleptik 1 – 5.Kata kunci: Tepung daging kerang, Organoleptik kerang, Solen sp., Derajad putih tepung.